Randomized Controlled Phase 2a Study of RPh201 in Previous Nonarteritic Anterior Ischemic Optic Neuropathy. Issue 3 (September 2019) - Rath, Eitan Z.; Hazan, Zadik; Adamsky, Konstantin; Solomon, Arieh; Segal, Zvi I.; Levin, Leonard A.
Abstract : Background: No proven treatment exists for nonarteritic anterior ischemic optic neuropathy (NAION), either in the acute or late phase. Objective: To assess safety and changes in visual function and structure after RPh201/placebo treatment in participants with previous NAION. Design and Setting: Phase 2a, single-site, prospective, randomized, placebo-controlled, double-masked trial (registration NCT02045212). Main Outcomes Measures: Early Treatment Diabetic Retinopathy Study best-corrected visual acuity (BCVA), visual fields, retinal nerve fiber layer, and visual evoked potential at weeks 13, 26, and after a 13-week wash-out ("off-drug") period; and safety. Study Population: Twenty-two participants aged 18 years or older with previous NAION. Intervention(s): RPh201 (20 mg) or placebo (cottonseed oil vehicle) administered subcutaneously twice weekly at the study site. Results: Thirteen men and 9 women were randomized, of which 20 completed all visits. The mean (±SD) age was 61.0 ± 7.6 years. In a post hoc analysis, after 26 weeks of treatment, BCVA improved by ≥15 letters in 4/11 (36.4%) eyes with RPh201, compared to 1/8 (12.5%) eyes with placebo ( P = 0.24). Overall, 7/11 (63.6%) of participants on RPh201 showed some improvement in BCVA, compared with 3/8 (37.5%) on placebo ( P = 0.26). Improvement in BCVA from a calculated baseline was 14.8 ± 15.8 letters for RPh201 and 6.6 ± 15.3 for placebo ( P = 0.27). Of the 154 adverse effects (AEs), 52 were considered related to the study procedures/treatment. Across the study and 1, 017 injections, the most frequently reported AE was injection site pain (23 events in 5 participants). There were no clinically significant changes in vital signs or laboratory values. Conclusions: This Phase 2a was designed to assess safety, feasibility, and explore potential efficacy signals in treating previous NAION with RPh201. No safety concerns were raised. The results support a larger trial in patients with previous NAION. Abstract : Supplemental Digital Content is Available in the Text.